Pengaruh Pemberian Kombinasi Ekstrak Rumput Mutiara (Hedyotis corymbosa Lamk) dan Meniran (Phyllanthus Niruri L.) terhadap Jumlah AgNOR Jaringan Adenokarsinoma Mammae Mencit C3H - Intan, Putri Reno; Winarno, M. Wien (Jurnal Kefarmasian Indonesia, 2014)
Cancer is one of the non-communicable diseases that has become a health problem in the world, including in Indonesia. Data World Health Organization (WHO) data in 2010 showed that cancer is the second leading cause of death after cardiovascular disease. Mean while, result at Basic Health Research Riset Kesehatan Dasar (Riskesdas) 2007 showed that cancer ranks sixth in the leading cause of death in Indonesia. Number of cancer patients in Indonesia continues to increase and is expected to be the main cause of the increasing economic burden, for the patient, family, and also country. Types of cancer in Indonesia is dominated by breast cancer (30%) cervical cancer (24%). This study aims to determine the effect of a combination of rumput mutiara (Hedyotis corymbosa Lamk) and meniran (Phyllanthus niruri L) against mammary adenocarcinoma in strain C3H mice. This study is an experimental study. The study sample consisted of 20 strains of C3H mice that were divided into 4 groups: control group (K) and three dose groups ( P1 - P3 ), namely : dose 750 ; 1500; 2250 mg/kg BW. Extract of the test material were given after the tumor is palpable, It was given to the mice for 19 days, once a day orally using a stomach sonde. The results of this study indicate that based on the average number of AgNOR mammary adenocarcinoma, the extract at a dose of 2250 mg/kg BW can reduce the proliferation of mammary tumor cells.